Mechanical strength and thermal stability of woven glass/kenaf fibre hybrid-reinforced nanoclay with epoxy composites - Tay, Chai Hua (2018)
This research investigates the hybrid effects between kenaf and glass fibres reinforced in modified epoxy filled with nanoclay. Kenaf fibres were treated with 2M Sodium Hydroxide (NaOH) solution. Epoxy was modified with 1 wt% silicon powder. Nanoclay loading was sonicated at 1.0 wt%, 3.0 wt% and 5.0 wt% with respect to epoxy. Three layers of glass fibres and two layers of kenaf fibres were lay-up alternately, which constitute to 20 wt% of composite. Composites were then fabricated using hot compression moulding technique. Analysis from Fourier Transform Infrared Spectroscopy (FTIR) revealed the absence of hemicellulose, lignin and hydroxyl functional group on TK/Ep composite. Flexural test revealed improved flexural strength and flexural modulus among treated kenaf composites. Impact test was conducted at two different energy levels of 15 J and 30 J. It was observed that composite dispersed with nanoclay is capable of sustaining both the loads. Morphology study through Field Emission Scanning Electron Microscope (FESEM) revealed the roughness on the surface of the fractured treated kenaf fibre. Thermogravimetric Analysis (TGA) result shows that the highest initial decomposition temperature was achieved by GUK/Ep-Si/1% nanocomposite, with 2.386% higher than GTK/Ep-Si/1% nanocomposite. Dynamic Mechanical Analysis (DMA) result reveals that the glass transition temperature (Tg) of 3G2UK/Ep-Si/1% nanocomposite is 6% higher than GTK/Ep-Si/1% nanocomposite which indicates the lower free volume in GUK/Ep-Si/1%. Overall, it can be concluded that composite with treated kenaf has better mechanical properties while composites with untreated kenaf possesses better thermal properties.